Application of the triple-probe technique to magnetized plasmas. (1st January 2023) - Dimitrova, M; Popov, Tsv K; Dejarnac, R; Kovačič, J; Ivanova, P; Gyergyek, T; Losada, U; Hidalgo, C; Panek, R; Stöckel, J
Abstract: The triple-probe technique (TPT) is a diagnostic widely used to determine the electron temperature in various devices and plasma conditions. It was developed for measurements in low-pressure gas-discharge plasmas in the absence of a magnetic field. This paper presents a comparison of the experimental results obtained by swept Langmuir probe (LP) measurements with those obtained by the TPT in magnetized plasmas in three experimental machines with different magnetic field magnitudes (0.01–1.15 T). The reliability of the triple-probe results for the electron temperature in tokamak plasmas at higher magnetic fields is discussed. It was found that the larger the magnetic field, the more the TPT overestimates the electron temperature compared with single swept LPs. The explanation proposed in this paper is based on a shift in the floating potential towards the plasma potential in the presence of a magnetic field, yielding a more positive voltage measured by the TPT and therefore higher electron temperatures. Using the extended formula for the electron probe current in the presence of a magnetic field a correction factor is derived such that the TPT yields a temperature similar to that of the swept LP techniques.